Optimizing Production Process through Production Planning and Inventory Management in Motorcycle Chains Manufacturer - Kurniawan, Shelvy; Raphaeli, Steven Sanjaya (Bina Nusantara University, 2018)
Based on the data, there were still shortages of production from year to year and demand wereunstable in motorcycle chains manufacturer in Indonesia. To overcome these problems, the purpose of this research was to make production planning and inventory control consisting of forecasting, aggregate planning, Master Production Schedule (MPS), and Material RequirementsPlanning (MRP). Forecasting used the additive decomposition method (average of all data), multiplicative decomposition (centered on moving average), and winter method (additive and multiplicative). Aggregate planning used chase strategy, level strategy, and transportation model. Moreover, MRP used lot for lot, Economic Order Quantity (EOQ), and Periodic Order Quantity (POQ) methods. The test shows several results. First, the best forecasting is additive decomposition (average of all data) with MAD value of 3.033,57, MSE with 13.590.490,and MAPE with 10,083%. Second, the best aggregate planning is transportation model with the total cost of Rp7.708.398.390,00. Last, the best MRP method is the lot for lot with total cost Rp7.162.567.653,00.